Highways Traffic Surveillance System (HTSS) using OpenCV - Zainab Nazar, Khalil Wafi; R. Badlishah, Ahmad, Prof. Madya, Dr.; Paulraj, Murugesa Pandiyan, Prof. Madya Dr. (Institute of Electrical and Electronics Engineers (IEEE), 2011)
Link to publisher's homepage at http://ieeexplore.ieee.org/